Social Regulation and Organizational Change: A Dynamic Interaction - Sadaoui, Smail; Boumegoura, Naim (جامعة زيان عاشور الجلفة, 2024)
Social regulation and organizational change dynamically interact within organizations. While social regulation provides stability through norms, values, and shared culture, it evolves during organizational change. This change, disruptive yet fostering adaptability and innovation, influences and is influenced by social regulation. Collaboration is central, aiding in navigating change and fostering solidarity. Despite challenges, such as tensions, constructive conflict management is crucial. In summary, this dynamic interaction shapes organizational life, promoting evolution and prosperity amidst constant change.
Keywords: التنظيم الاجتماعي -- التغيير التنظيمي -- العلاقات الاجتماعية -- الصراعات التنظيمية